Psychological Interventions for Prenatal Anxiety in Latinas and Black Women: A Scoping Review and Recommendations - Ponting, Carolyn; Urizar, Guido G.; Dunkel Schetter, Christine (Frontiers in Psychiatry, 2022)
Anxiety symptoms are common among pregnant women worldwide. In the United States, prenatal anxiety symptoms tend to be elevated among Black and Latin American women as compared to non-Latina White women. Despite the high prevalence of anxiety and associations with adverse maternal and offspring outcomes, interventions have not been developed or tailored sufficiently to women of color who need efficacious treatment. This paper provides a scoping review of articles published since 2017 that test the effects of randomized and non-randomized psychological interventions designed to reduce prenatal anxiety in samples comprised primarily of ethnic/racial minority women. We also review published protocols of planned psychological interventions to reduce prenatal anxiety in order to highlight novel approaches. In addition to summarizing intervention efficacy and participant acceptability, we highlight gaps in the literature which, if addressed, could improve perinatal mental health equity. Finally, we discuss future directions in prenatal anxiety intervention science beginning preconception including intervention design and prevention models.